Analysis of Peristaltic Motion of a Nanofluid with Wall Shear Stress, Microrotation, and Thermal Radiation Effects - C. Dhanapal; J. Kamalakkannan; J. Prakash; M. Kothandapani (Applied Bionics and Biomechanics)
This paper analyzes the peristaltic flow of an incompressible micropolar nanofluid in a tapered asymmetric channel in the presence of thermal radiation and heat sources parameters. The rotation of the nanoparticles is incorporated in the flow model. The equations governing the nanofluid flow are modeled and exact solutions are managed under long wavelength and flow Reynolds number and long wavelength approximations. Explicit expressions of axial velocity, stream function, microrotation, nanoparticle temperature, and concentration have been derived. The phenomena of shear stress and trapping have also been discussed. Finally, the influences of various parameters of interest on flow variables have been discussed numerically and explained graphically. Besides, the results obtained in this paper will be helpful to those who are working on the development of various realms like fluid mechanics, the rotation, Brownian motion, thermophoresis, coupling number, micropolar parameter, and the nondimensional geometry parameters.